Study on AgInZnS-Graphene Oxide Non-toxic Quantum Dots for Biomedical Sensing - Song, Chi; Luo, Haoyue; Lin, Xiaogang; Peng, Zhijia; Weng, Lingdong; Tang, Xiaosheng; Xu, Shibin; Song, Ming; Jin, Lifeng; Zheng, Xiaodong (Frontiers in Chemistry, 2020)
In recent years, non-toxic quantum dot has caught the attention of biomedical fields. However, the inherent cytotoxicity of QDs makes its biomedical application painful, and is a major drawback of this method. In this paper, a non-toxic and water-soluble quantum dot AgInZnS-GO using graphene oxide was synthesized. A simple model of state complex was also established, which is produced through a combination of quantum dots and protein. The interaction between AIZS-GO QDs and human serum albumin (HSA) has significant meaning in vivo biological application. Herein, the binding of AIZS-GO QDs and HSA were researched using fluorescence spectra, Uv-visible absorption spectra, FT-IR spectra, and circular dichroism (CD) spectra. The results of fluorescence spectra demonstrate that AIZS-GO QDs have an obvious fluorescence quenching effect on HSA. The quenching mechanism is static quenching, which implies that some type of complex was produced by the binding of QDs and HSA. These results were further proved by Uv-visible absorption spectroscopy. The Stern-Volmer quenching constant Ksv at various temperatures (298 K, 303 K, 308 K) were acquired from analyzing Stern-Volmer plots of the fluorescence quenching information. The Van't Hoff equation could describe the thermodynamic parameters, which demonstrated that the van der Waals and hydrogen bonds had an essential effect on the interaction. FT-IR spectra and CD spectra further indicate that AIZS-GO QDs can alter the structure of HSA. These spectral methods show that the quantum dot can combine well with HSA. The experimental results showed that AgInZn-GO water-soluble quantum dots have good biocompatibility, which can be combined with proteins to form new compounds which have no cytotoxicity and biological practicability. It provides an important basis for the combination of quantum dots and specific proteins as well as fluorescent labeling.